Three new jatrophane-type diterpenes from Euphorbia pubescens - Valente, C (2015)
Three new macrocyclic jatrophane diterpene polyesters, named pubescenes A (1), B (2), and C (3), and the known compounds indole-3-aldehyde and scopoletin have been isolated and characterised from the whole dried plant of Euphorbia pubescens. The structures of the new compounds were established by spectroscopic means including 2D-NMR techniques such as COSY, HMQC, HMBC and NOESY experiments. Compounds 1-3 were evaluated for their in vitro effect on the growth of three human cancer cell lines MCF-7 (breast), NCI-H460 (lung) and SF-268 (CNS) as well as for their capacity to interfere with the proliferation of human peripheral blood lymphocytes. They exhibited a moderate growth inhibitory effect on the cancer cell line NCI-H460. No effect was observed on the mitogenic response of human lymphocytes to PHA.